Smart management system in electric market considering customer demand response. (April 2022) - Liu, Fei; Cheng, Guanghua; Pan, Bing
Highlights: The present study is a complement to other studies that have been published in scientific journals related to the solution of the EGIP based on AC modeling of the problem and simultaneous line and generator attacks. The assessed resilience of power grids under deliberate attacks is examined using novel measures. DERs are offered to enhance the grid's resilience as a reaction strategy for system operators. Abstract: The case of a disruptive agent that tries to maximize damage to the system (determined by total network operating costs), while the system operator is taking the appropriate steps to minimize the consequences of the attack, is considered in the present study. A bi-level optimization problem is used to model the interaction between the two agents. One aspect of this is that the destructive factor is involved in the top-level optimization problem and should choose that lines and generators to disable (with a restricted destructive budget). Therefore, a new scheme is proposed for maximizing the system's resilience under intentional attacks, by implementing distributed energy resources (DERs) such as distributed generation, and demand response. Also, the grey wolf optimization algorithm is used to solve the optimization problem in the paper. By allocating DERs in islands produced by destroyed lines and generators, three metrics have been suggested in order to evaluate resilience. Graphical abstract: Image, graphical abstract